2018
DOI: 10.1016/j.virol.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative assessment of dynamical differences of RSV infections in vitro and in vivo

Abstract: Experimental results in vitro and in animal models are used to guide researchers in testing vaccines or treatment in humans. However, viral kinetics are different in vitro, in animals, and in humans, so it is sometimes difficult to translate results from one system to another. In this study, we use a mathematical model to fit experimental data from multiple cycle respiratory syncytial virus (RSV) infections in vitro, in african green monkey (AGM), and in humans in order to quantitatively compare viral kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…We fit the viral replication data to a viral kinetics model used in Baccam et al. ( 2006 ), González-Parra and Dobrovolny ( 2018 ) and Pinilla et al. ( 2012 ), V is the virus population (in f.f.u./mL) as a function of time t (in days).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We fit the viral replication data to a viral kinetics model used in Baccam et al. ( 2006 ), González-Parra and Dobrovolny ( 2018 ) and Pinilla et al. ( 2012 ), V is the virus population (in f.f.u./mL) as a function of time t (in days).…”
Section: Resultsmentioning
confidence: 99%
“… 2006 ). Recently, mathematical models have also be generated for RSV that predict both in vitro and in vivo replication dynamics (González-Parra and Dobrovolny 2019 , 2018 ). However, the recent discovery of appreciable differences in stability between RSV strains led us to hypothesize that both temperature and pH also play important strain-specific roles in viral clearance of RSV infection.…”
Section: Introductionmentioning
confidence: 99%
“…We use a within host model of viral infection with the method of stages to generate gamma distributions for the cell transitions from eclipse to infectious and infectious to dead. This model has previously been used to analyse other respiratory infections such as influenza ( Pinilla et al, 2012 , Paradis et al, 2015 , Beggs and Dobrovolny, 2015 , González-Parra et al, 2018 ), and RSV ( González-Parra et al, 2018 , González-Parra and Dobrovolny, 2018 ). The system of differential equations is 2 2 where the target cells T are infected by the virus V at an infection rate β .…”
Section: Methodsmentioning
confidence: 99%
“…The already cited prospective viral surveillance study of Khuri-Bulos and colleagues reported a significantly lower presence of fever but a high probability of cough, shortness of breath, and flaring in patients with RSV infection [58]. It has been observed that RSV-A causes more severe illness than RSV-B; in fact, the two serotypes elicit a different response in terms of cytokine and neutrophil production [74,79].…”
Section: Clinical Manifestation Of Respiratory Syncytial Virus (Rsv)mentioning
confidence: 99%
“…These infections can appear every two or three years, with different clinical RSV presents direct cytopathic activity, but signs and symptoms, which are virus dependent, are also due to the local host inflammatory response (innate and adaptative immune responses) created by its presence in airway epithelial cells [69][70][71][72][73]. Many in vitro and animal models have been employed to infer the pathological pathway of RSV, though its interaction with human hosts, and particularly with children, differs greatly from other models [74].…”
Section: Clinical Manifestation Of Respiratory Syncytial Virus (Rsv)mentioning
confidence: 99%